Performance Analysis of Photovoltaic Water Heating System - Tomas Matuska; Borivoj Sourek (International Journal of Photoenergy)
Performance of solar photovoltaic water heating systems with direct coupling of PV array to DC resistive heating elements has been studied and compared with solar photothermal systems. An analysis of optimum fixed load resistance for different climate conditions has been performed for simple PV heating systems. The optimum value of the fixed load resistance depends on the climate, especially on annual solar irradiation level. Use of maximum power point tracking compared to fixed optimized load resistance increases the annual yield by 20 to 35%. While total annual efficiency of the PV water heating systems in Europe ranges from 10% for PV systems without MPP tracking up to 15% for system with advanced MPP trackers, the efficiency of solar photothermal system for identical hot water load and climate conditions is more than 3 times higher.